Monitoring of the changes in potential environmental risk of some heavy metals in water and sediments of Burullus Lake, Egypt - Melegy, Ahmed A. (2021)
The mean concentrations of heavy metals in Burullus bottom sediments in 2010 were arranged in descending order as follows: Fe > Mn > Cr > Zn > Ni > Cu > Pb > Cd, while the descending order in 2012 is Fe > Mn > Zn > Cr > Cu > Ni > Pb > Cd, as well as the descending order in 2015 is Fe > Mn > Zn > Cr > Ni > Pb > Cu > Cd. The Fe is the highest concentration in all years.